2013
DOI: 10.1063/1.4817722
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid heterostructures based on aromatic polyimide and semiconductor CdSe quantum dots for photovoltaic applications

Abstract: Articles you may be interested inUnderstanding the electronic structure of CdSe quantum dot-fullerene (C60) hybrid nanostructure for photovoltaic applications Organic/inorganic hybrid pn-junction between copper phthalocyanine and CdSe quantum dot layers as solar cells J. Appl. Phys. 112, 044507 (2012); 10.1063/1.4747835 Improved efficiency of hybrid solar cells based on non-ligand-exchanged CdSe quantum dots and poly(3-hexylthiophene) Appl. Phys. Lett. 96, 013304 (2010); 10.1063/1.3280370 Effect of ZnS coating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…Hybrid organic–inorganic materials have been intensively investigated for at least three decades. Nevertheless, new interesting compounds are still being discovered due to a large variety of available organic and inorganic components, as well as emerging synthesis techniques using different experimental conditions. It has been shown that hybrid organic–inorganic compounds play a prominent role in the development of new advanced functional materials. Because of the complementary properties of the organic (flexibility and structural diversity) and inorganic (rigidity and stability) components, these materials are suitable for many applications in areas such as optoelectronics, environmental protection, or catalysis. , The structure diversity of hybrid materials gives almost limitless possibilities of obtaining crystals with different properties. However, controlling the magnitude of a particular physical effect often requires steering of molecular self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid organic–inorganic materials have been intensively investigated for at least three decades. Nevertheless, new interesting compounds are still being discovered due to a large variety of available organic and inorganic components, as well as emerging synthesis techniques using different experimental conditions. It has been shown that hybrid organic–inorganic compounds play a prominent role in the development of new advanced functional materials. Because of the complementary properties of the organic (flexibility and structural diversity) and inorganic (rigidity and stability) components, these materials are suitable for many applications in areas such as optoelectronics, environmental protection, or catalysis. , The structure diversity of hybrid materials gives almost limitless possibilities of obtaining crystals with different properties. However, controlling the magnitude of a particular physical effect often requires steering of molecular self-assembly.…”
Section: Introductionmentioning
confidence: 99%
“…QDs can be used for development of both photoactive and transport layers. The photoactive layer can be prepared using QD–polymer mixtures , and ternary blends . For example, in the latter case, doping of graphitic carbon nitride QDs into polymer–fullerene blends increases the solar cell efficiency to 9.18% due to the combined improvements in nanomorphology, electron transfer, and charge carrier transport .…”
mentioning
confidence: 99%
“…Благодаря уникальным оптическим свойствам, а также высокой фотостабильности коллоидные квантовые точки (КТ) в настоящее время являются одним из перспективных материалов для применения в опто-электронных устройствах [1][2][3][4][5]. Большой интерес в последнее время направлен на изучение КТ на основе халькогенидов свинца, которые способны поглощать свет в ИК-области спектра, что делает их весьма привлекательным материалом для использования в фотовольтаических устройствах [2][3][4], ИК-фотодетекторах [5], а также при разработке светодиодов нового поколения [6]. Исследования нового типа конден-сированных сред -пленок КТ -весьма актуальны как с фундамен-тальной, так и с прикладной точки зрения, поскольку пленки КТ по своим свойствам качественно отличаются от традиционных твердых…”
Section: поступило в редакцию 26 апреля 2017 гunclassified
“…Показано, что уменьшение длины лигандов в 4 раза приводит к значительному убыванию времени затухания люминесценции, а также экспоненциальному усилению проводимости. DOI: 10.21883/PJTF.2017.19.45077.16836 Благодаря уникальным оптическим свойствам, а также высокой фотостабильности коллоидные квантовые точки (КТ) в настоящее время являются одним из перспективных материалов для применения в опто-электронных устройствах [1][2][3][4][5]. Большой интерес в последнее время направлен на изучение КТ на основе халькогенидов свинца, которые способны поглощать свет в ИК-области спектра, что делает их весьма привлекательным материалом для использования в фотовольтаических устройствах [2-4], ИК-фотодетекторах [5], а также при разработке светодиодов нового поколения [6].…”
unclassified